Upaya Meningkatkan Kemampuan Membaca Menggunakan Media Audio Visual Dengan Materi Membaca Kosakata Pada Siswa Kelas IV SD Negeri 21 SKPG SP.2 Emparu - Anjelin Elvy Alvina; Lia Rismawati (Literasi: Jurnal Pendidikan Guru Indonesia, 2025)
This study aims to improve the vocabulary reading skills of fourth-grade students at SD Negeri 21 SKPG SP2 Emparu through the use of audiovisual media. The main problem addressed is the students’ low reading skills, characterized by poor word pronunciation, low learning focus, and weak classroom communication ethics. The research employed the Classroom Action Research (CAR) method based on the Kemmis and McTaggart model, conducted over two cycles. Each cycle consisted of several stages: planning, action, observation, and reflection. Data collection instruments included student worksheets, multiple-choice evaluation questions, and observation sheets of student activities. The results of the study showed a significant improvement from the first to the second cycle. In the first cycle, the student learning mastery rate reached only 45%, with an average score of 64.25. After improving the learning process by incorporating small group discussions and active guidance during video viewing, the mastery rate increased to 90% with an average score of 83 in the second cycle. These results demonstrate that audiovisual media is effective in enhancing students' vocabulary comprehension and active participation in Indonesian language learning. This study recommends the use of audiovisual media as an adaptive and contextual learning strategy in primary school settings, especially in remote areas.